ANTIBIOTIC RESISTANCE: PUBLIC KNOWLEDGE AND PERCEPTION OF ANTIBIOTIC USE IN RELATION TO SOCIAL DETERMINANTS - Shan, Hina `; Mashhadi, Syed Fawad; Maqbool, Saadia (Pakistan Armed Forces Medical Journal, 2019)
Objective: To assess the knowledge and perception of appropriate use of antibiotics, when to discontinue the course once the treatment begins and the conditions/illnesses antibiotics treat in relation to social determinants in residents of Wah.Study Design: Cross sectional-analytical study.Place and Duration of Study: One year from January to December 2017 in Wah, Pakistan.Material and Methods: A two stage cluster random sampling technique was used. A total of 400 participants aged 16 years and older completed the validated questionnaire. Chi-square test of significance was applied to determine the relationship between social variables with dependent variables, p-value